2021
DOI: 10.3389/fcvm.2021.636491
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Vitamin K Antagonists vs. Novel Oral Anticoagulants in Patients With Left Ventricular Thrombus: A Meta-Analysis

Abstract: Aims: A meta-analysis was conducted to evaluate the safety and efficacy of novel oral anticoagulants (NOACs) compared with vitamin K antagonists (VKAs) in patients with left ventricular thrombus (LVT).Methods and Results: We searched PubMed, Web of Science, and Cochrane Library for cohort studies comparing the use of VKAs vs. NOACs for the treatment of LVT from the earliest date available to September 30, 2020. The predetermined efficacy and safety outcomes included thromboembolic events, resolution of LVT, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A few meta-analyses have drawn varied conclusions in terms of efficacy and safety between DOACs and VKAs, 35,36 predominantly suggesting that DOACs use may be promising when treating patients with LVT. However, no RCTs were included in the meta-analysis of Xuan et al, 35 resulting in a lack of clinical evidence. Almost 50% of the studies included in the study by Michael et al involved abstracts without complete experimental data, 36 which may influence the generalizability of their results.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few meta-analyses have drawn varied conclusions in terms of efficacy and safety between DOACs and VKAs, 35,36 predominantly suggesting that DOACs use may be promising when treating patients with LVT. However, no RCTs were included in the meta-analysis of Xuan et al, 35 resulting in a lack of clinical evidence. Almost 50% of the studies included in the study by Michael et al involved abstracts without complete experimental data, 36 which may influence the generalizability of their results.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several case studies, observational studies, and randomized control trials (RCTs) have suggested analogous or contradictory safety and efficacy when comparing DOACs with VKAs to treat LVT. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 A few meta‐analyses have drawn varied conclusions in terms of efficacy and safety between DOACs and VKAs, 35 , 36 predominantly suggesting that DOACs use may be promising when treating patients with LVT. However, no RCTs were included in the meta‐analysis of Xuan et al ., 35 resulting in a lack of clinical evidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are used to prevent and treat thromboembolic disorders, such as stroke, deep vein thrombosis, and pulmonary embolism. Some of the NOACs that have been approved [ 182 ] are: Dabigatran etexilate: a direct thrombin inhibitor that is approved for stroke prevention in atrial fibrillation, the prevention and treatment of venous thromboembolism, and the prevention of thromboembolism after hip or knee replacement surgery [ 183 ]; Rivaroxaban: a direct factor Xa inhibitor that is approved for stroke prevention in atrial fibrillation, the prevention and treatment of venous thromboembolism, the prevention of thromboembolism after hip or knee replacement surgery, and the secondary prevention of acute coronary syndrome [ 182 ]; Apixaban: a direct factor Xa inhibitor that is approved for stroke prevention in atrial fibrillation, the prevention and treatment of venous thromboembolism, and the prevention of thromboembolism after hip or knee replacement surgery [ 184 ]; Edoxaban: a direct factor Xa inhibitor that is approved for stroke prevention in atrial fibrillation and the treatment of venous thromboembolism [ 185 ]. …”
Section: Management Of Npslementioning
confidence: 99%
“…Most recently, the breakthrough of 2 novel randomized controlled trials have shown DOACs to be a promising treatment for LV thrombus. They also appealed that the optimal timing and type of anticoagulation for LV thrombus, and the role of screening for high-risk patients, should be tested in more prospective, randomized trials (17)(18)(19)(20)(21)(22)(23)(24)(25). We analyzed the relationship between baseline medication and mortality within 1 month and found aspirin/clopidogrel/ticagrelor + anticoagulant (HR, 0.066; 95% CI 0.011-0.403; p = 0.003) and aspirin + clopidogrel/ticagrelor + anticoagulant (HR, 0.059; 95% CI 0.004-0.804; p = 0.034) had protective effect on mortality.…”
Section: Anticoagulation Therapymentioning
confidence: 99%